Mobile Robot Navigation And Mapping - Abu Bakar, Dzul Fahmi (Universiti Sains Malaysia, 2006)
The purpose of the project is to create a mobile robot that has artificial intelligent can complete the objective of the project that is to navigate through a simple maze using sensors to detect and avoid a simple maze. A simple maze means that the wall made up of only one surface while a complex maze is a maze that made of at least two surfaces or more. The robot movement is controlled by two motors where the speed and direction of the motors is controlled by a microcontroller according to the signal given. The signal is given by three sensors that been position to the robot body to the left, in front and right. The sensors will be activating if there are any object in the path. In this project the robot will use the BASIC Stamp II that been produced by Parallax Incorporation and has 2048 bit internal memory. This micro controller can execute more complex programming like data logger. PBASIC assembly language will be use in this project.